Pengaruh Desain Bantal dan Posisi Tidur Terhadap Intensitas Nyeri Leher Non Spesifik pada Mahasiswa: The Effect of Pillow Design and Sleeping Position on the Intensity of Non-Specific Neck Pain in College Students - Melani Dwita Sari; Gita Diah Prasasti; Miranti Dewi Pramaningtyas (Journal of Health, 2026)
Background: Non-specific neck pain is non-specific neck pain spreads to the upper limbs, is influenced by sleep quality.  The use of pillows is very important for comfort and promotes good sleep quality. Sleeping position also plays an important role in the incidence of non-specific neck pain apart from pillow design that is not ideal. Objectives: To determine the effect of pillow design (type, size, height) and sleeping position on the intensity of non-specific neck pain in students. Methods: This research was a cross-sectional study conducted in August 2023. The population of this study were students from the Faculty of Medicine, Universitas Islam Indonesia. The total sample that met the criteria were 229 respondents. All samples were analyzed univariately and bivariately using the Chi-Square test. Results: This study found that the variables of pillow height and pillow size significantly affected the incidence of neck pain, with p-values of 0.037 and 0.010, respectively. Additionally, the type of pillow and size of the pillow significantly affected the intensity of neck pain, with p-values of 0.011 and 0.000, respectively. Conclusions: Variables that influence the incidence of neck pain are pillow height and pillow size. Further research is recommended to use a uniform pillow design for all participants.